1985
DOI: 10.1056/nejm198501173120302
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Requirement for Taurine in Patients Receiving Long-Term Parenteral Nutrition

Abstract: Animals fed diets lacking the amino acid taurine have low plasma and tissue levels of taurine and ultimately have retinal dysfunction. Since parenteral nutrition does not ordinarily provide taurine, we looked for evidence of taurine deficiency in 21 children and 23 adults undergoing long-term parenteral nutrition at home for an average of 27 +/- 23 (S.D.) months. The fasting plasma taurine level was reduced in children as compared with controls (26 +/- 13 vs. 57 +/- 16 mumol per liter, P less than 0.001). In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
82
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(83 citation statements)
references
References 7 publications
0
82
0
1
Order By: Relevance
“…Its plasma levels are maintained within a normal range through protein intake, and de novo synthesis is limited by the activity of hepatic cysteinesulphinic acid decarboxylase, which is low in humans. Taurine depletion can occur rapidly (10), possibly leading to retinal, cardiac, neural, immune, and hemostatic dysfunction (4,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Its plasma levels are maintained within a normal range through protein intake, and de novo synthesis is limited by the activity of hepatic cysteinesulphinic acid decarboxylase, which is low in humans. Taurine depletion can occur rapidly (10), possibly leading to retinal, cardiac, neural, immune, and hemostatic dysfunction (4,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…In the clinical study of Geggel et al (34), children re ceiving total parenteral nutrition without taurine exhi bited a low concentration of plasma taurine (47% of normal) and a slight ERG abnormality, which reversed after the addition of taurine in doses of 150 to 187.5 mg/kg/day for 12 to 14 weeks. These clinical doses were close to the dose of 30 mg/animal/day used here.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas it is obvious that these retinal disorders are elicited by GES in rats, it is yet not known if administration of taurine can normal ize the decreased tissue taurine levels as well as the ERG disorder in taurine-deficient animals. On the other hand, it has been reported that a slight ERG dis order and low plasma taurine levels in human infants treated with taurine-free amino acid solutions in long term parenteral nutrition are normalized by addition of taurine to the solution (34).…”
mentioning
confidence: 99%
“…Most overgrowth (Sheikh, 1981) compromise the intake of dietary mammalian species are resistant to dietary manipulation taurine and lead to visual defects. Human infants and but, in rats and mice, the administration of a transport children maintained on taurine-free total parenteral 4358 nutrition show abnormalities in the electroretinogram and fundus changes are first seen as mild granularity of the retinal pigment epithelium (RPE) (Geggle, Ameant, Heckenlively & Kopple, 1982a). In man, all the ocular manifestations described above can be reversed by dietary supplementation.…”
mentioning
confidence: 90%
“…In man, pathological and is essential for their survival (Wright, Tallan & Lin, conditions such as bowel resection (Geggle, Heckenlively, 1986). In the cat, nutritional deficiencies are associated with Martin, Ameant & Kopple, 1982b; Geggle, Ameant, initial loss of central vision followed by progressive loss in Heckenlively, Martin & Kopple, 1985) or colonic bacterial the periphery (Hayes, Carey & Shmidt, 1975). Most overgrowth (Sheikh, 1981) compromise the intake of dietary mammalian species are resistant to dietary manipulation taurine and lead to visual defects.…”
mentioning
confidence: 99%